Antipsychotic utilisation and persistence in Australia: A nationwide 5-year study. (September 2022) - Taylor, Mark; Dangelo-Kemp, Dante; Liu, Dennis; Kisely, Steve; Graham, Simon; Hartmann, Jodie; Colman, Sam
Objectives: To evaluate the utilisation and persistence of antipsychotics for the treatment of schizophrenia in Australia. Methods: A retrospective study using the Australian Pharmaceutical Benefits Scheme database of a representative 10% sample. All adults with schizophrenia who were dispensed three or more supplies of oral (including clozapine) or long-acting injectable antipsychotics between 1 June 2015 and 31 May 2020 were included. Persistence time in treatment was evaluated using survival analysis and Cox hazard ratios. Results: In all, 26, 847 adults with schizophrenia were studied. Oral second-generation antipsychotics were more frequently dispensed than the other antipsychotic groups studied. Median treatment persistence times were 18.3 months for second-generation antipsychotic long-acting injectables, 10.7 months for oral second-generation antipsychotics and were significantly lower for both formulations of first-generation antipsychotics at 5.2 months (long-acting injectables) and 3.7 months (oral). The median persistence time for clozapine was significantly longer than all other antipsychotics groups. Conclusions: Oral second-generation antipsychotics and second-generation antipsychotic long-acting injectables accounted for over 75% and 13% of all antipsychotics in Australia, respectively. Concerns over medication adherence and subsequent relapse have not translated into increased long-acting injectable usage despite their significantly longer persistence. Clozapine, the single most 'persistent' antipsychotic, was only used in 9% of people, although up to a third of all cases are likely to be treatment-resistant. Our data suggest clinicians should give consideration to the earlier use of second-generation antipsychotic long-acting injectables and clozapine, to ameliorate prognosis in schizophrenia.